PEMODELAN FASIES BATUPASIR RESERVOIR LAPANGAN âFITRIâ, BENGKALIS TROUGH, CEKUNGAN SUMATERA TENGAH - , FITRIANI INDAH PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Lakat and Tualang Sandstone is the most productive reservoirs in Fitri Field, which is heterogenous both vertical and lateral,cause some difficulties in oil filed development. So far, it has never been made sedimentary facies model of Lakat and Tualang Formation in Bengkalis Trough, especially in Fitri Field. Sequence stratigraphy concept will be used in detail facies modelling to distinguish sandbody of Lakat and Tualang Formation based on its genetical unit. Lakat and Tualang Formation consists of alternating sandstones, siltstones and shales, deposited on fluvial, delta, estuarine to beach environment at Late Oligocene untill Early Miocene. In sequence stratigraphy interepretation of Lakat and Tualang Formation, there are 2 (two) allocyclic sequences, influenced by eustacy. Based on sequence stratigraphic marker, flooding surface (FS) and sub-flooding surface (sub-FS), 7 (seven) sand reservoirs can be determinated. These sands are L, K, J, I, H, G, E and D Sands with facies: Distributary Mouth Bar, Mouth Bar, Distributary Channel, Tidal Estuarine and Storm Deposit. Generally, the facies geometry of sandstone are elongate and perpendicular to shoreline, related to tidal energy influence the deltaic system from northern Bengkalis (interpretated as metamorf basement high from Sundaland). Facies modelling result an imagine of facies provenance, distribution of facies thickness and dynamic sedimentation of Lakat and Tualang Formation as a hydrocarbon reservoir, that expected helpful for development of âFitriâ Field further.